MERUMUSKAN PRINSIP-PRINSIP DAN KRITERIA EKOWISATA DAERAH BALI - Gde Raka Dalem, Anak Agung (Bumi Lestari, 2012)
Principles and criteria of ecotourism were set by running a workshop on ecotourism training in Sanur, Bali, between September 3-5, 2002, involving participants from a wide range of backgrounds: government, tourism industry, academics, and NGOs. The workshop was aimed to set up the principles and criteria which is suitable for Bali. Principles of ecotourism as output of the workshops are as follows: (1) Have a concern, commitment, and responsibility to conservation of nature and culture; (2) Provide an interpretation which make tourists possible to enjoy nature and foster their interest on conserving nature; (3) Continuously provide contribution to local community as well as empowering local community; (4) Sensitive and respect to local socio-culture and local religious tradition; (5) Abide to law or regulations; (6) Its development must be based on consultation and approved by local community; (7) Continuously provide satisfaction to the costumers/tourists; (8) Honestly and accurately marketed and promoted, so meets tourist’s expectation (responsible marketing); (9) Apply harmonious and balanced management based on the Tri Hita Karana concept. Criteria of ecotourism were then formulated based on those principles.
Keywords: ecotourism, principles, criteria, Bali, IES, MEI